Art and culture critical essays - Greenberg, Clement (Beacon Paperback, Vol. 212, 1961)
Clement Greenberg is, internationally, the best-known American art critic popularly considered to be the man who put American vanguard painting and sculpture on the world map.... An important book for everyone interested in modern painting and sculpture.'—The New York Times